PEMODELAN FORMULA MATEMATIK UNTUK MENENTUKAN NILAI BUKU AKTIVA TETAP DAN ALGORITMANYA DALAM BAHASA PEMROGRAMAN QUICK BASIC - Yudha Herlambang, SE., Ak., ST., MT. (EKUITAS (Jurnal Ekonomi dan Keuangan), 2007)
According to General Accepted Accounting Priciples (GAAP), we realize that Fix Assets have been used during periodic useful live which be allocated for cost was called Deppreciation Cost .For the Fixed Assets which be depreciated will result the final Value of the Assets mentioned Book Value. The Book Value of Fix Assets in the first year was called the Historical Cost.The Book Value in each periodcan be calculated by using conventional method, we can make the tabulation chronologically until the end of useful life. In this paper, the author will design the mathematical formulation for determining the Book Value Directly at the year-t or Book Value Equation referred  to the function t(time) without tabulation process, for each depreciation method used in Accounting Principle .In other side, the author will also design the programming and algorithm in Computer Language by using Quick Basic Software. And the last the author will test the validity of program and mathematic formulation by comparing the result with the result of conventional method (tabulation method).